Mechanical, dynamical, thermal, electronic, magnetic and optical properties of XFeSb (X = Nb, V, Ta) half-heusler compounds: First-principles study - Rijal, Om Shree; Neupane, Hari Krishna; Poudel, Ganesh; Yadav, Sukrit Kumar; Parajuli, Rajendra (Himalayan Physics, 2025)
Half-Heusler (HH) compounds are promising candidates for thermoelectric, electronic, and energy-related applications. In the present work, we explored the structural, mechanical, dynamical, thermal, electronic, and magnetic properties of NbFeSb, VFeSb, and TaFeSb half-Heusler (HH) compounds using DFT methods through VASP software. For the structural properties, we calculated the ground-state energy and the bond lengths between nearest-neighbor atoms in the materials. We found that the studied compounds are structurally stable. The mechanical properties of the materials are examined through the calculations of their elastic constants and modulus of rigidity. It is found that NbFeSb, VFeSb, and TaFeSb are mechanically stable. Based on the calculated values of modulus of rigidity and anisotropic index, all the compounds exhibit hardness and anisotropic properties. Based on Pugh's and Poisson's ratios, NbFeSb and TaFeSb have ductile properties, whereas VFeSb exhibits a brittle nature. The dynamical properties of the materials are examined through their phonon dispersion curves and are found to be dynamically stable. Moreover, we have determined the phonon velocities and Debye temperature of the considered compounds and found that NbFeSb, VFeSb, and TaFeSb exhibit good thermal properties. The electronic properties of NbFeSb, VFeSb, and TaFeSb are explored through the analysis of their band structures and DOS plots; they are found to be small band-gap semiconducting materials. The magnetic properties of the materials are calculated by analyzing their DOS and PDOS plots and are found to be non-magnetic materials.